THE USE OF DIGITAL TECHNOLOGIES IN SOLVING PRACTICAL PROBLEMS (European Journal of Economics, Finance and Business Development, 2024)
The article examines the impact of digitalization on various aspects of public life in Uzbekistan. Describing the current state of digital transformation in the country, they pay attention to the use of digital technologies in business and the economy. Discusses successful cases and innovative projects aimed at improving access to services, optimizing processes and increasing efficiency. Analyzing the challenges and prospects for development, the authors emphasize the importance of government support and investment in the digital sphere to achieve the country's strategic development goals. This article provides a useful overview for managers, specialists and researchers interested in the role of digital technologies in modern society in Uzbekistan.